PENGARUH PENERIMAAN PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH PROPINSI SUMATERA BARAT TAHUN 2010 - 2015 - Ingra Sovita, Enny Arita Mailinarti (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2017)
The purpose of this study to analyze the influence of local tax revenue to the Local RevenueWest Sumatra province in 2010 - 2015. Type a descriptive quantitative research data. Datacollection techniques used documentation studies and surveys using secondary data suchas time series data obtained through library research and then processed with descriptivestatistics. The dependent variable revenue (Y) and the motor vehicle tax-free variable (X).Before the data is processed first performed classical assumption in the form of normalitytest. Hypothesis testing using t test partially with significance level of 5% and a coefficientdetermination. The results showed that the original income and taxes are normallydistributed by Kolmogorov Smirnov. Local tax revenue correlates strongly with revenue(0.777) and R-square value of 0.604. T test results showed that the significant effect on thelocal tax Local Revenue West Sumatra province with the regression equation Y =1,539E11 + 0.379 X + e.Keywords : local tax revenue ; locally-generated revenue